MEDIASI JOB DESCRIPTION DAN LOYALITAS KARYAWAN PADA PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DI PT. BALI ADVENTURE TOURS - I Nyoman Suarjaya; I Made Bayu Wisnawa (Forum Manajemen, 2022)
This study aims to analyze the mediation of job descriptions and employee loyalty on the influence of organizational culture on employee performance at PT. Bali Adventure Tours. The problem of this research refers to the phenomenon that occurs where employee performance is low, indicated by the percentage of employees in each department receiving a fairly high warning letter, both related to organizational culture issues, job descriptions and employee loyalty. The three types of violations include those used by management as a reference to measure employee performance through performance evaluation. The disproportional sampling technique was carried out on 86 respondents who were employees of PT. Bali Adventure Tours. The analysis technique used is descriptive analysis technique and inferential analysis technique, path analysis. The findings of this study indicate that the direct relationship of organizational culture has a positive and significant effect on job descriptions, organizational culture has a positive and significant influence on employee loyalty, employee loyalty has a positive and significant influence on employee performance. Organizational culture and job description have a negative and significant influence on employee performance. The indirect relationship of organizational culture through job description mediation to employee performance has a positive and significant influence. Likewise, organizational culture mediated by employee loyalty on employee performance has a positive and significant influence. Suggestions from this research is the company through the existing organizational culture is always able to continue to grow a sense of loyalty of its employees so as to increase the positive and significant influence on the performance of its employees.